Addition of two negative integers
Steps of addition of Negative Integers:
Step 1: Add the integers (ignoring subtraction operator)
Step 2: Put Subtraction operator on the left side of obtained integer because given integers are negative integers.
Example 1 : Add (-5) and (-3)
Answer = Write the given integers in addition expression and we get:
(-5) + (-3)
Ignoring the Subtraction operator (-) and add the given integers (-5) and (-3) and we get
= 5 + 3 = 8
Now, since both the given integers are negative, so put Subtraction operator(-) on the left side of obtained integer and we get;
= (-8)
Hence, (-5) + (-3) = (-8)
Example 2 : Add (-16) and (-15)
Answer = Write the given integers in addition expression and we get:
(-16) + (-15)
Ignoring the Subtraction operator (-) and add the given integers (-16) and (-15) and we get
= 16 + 15 = 31
Now, since both the given integers are negative, so put Subtraction operator(-) on the left side of obtained integer ans we get:
= (-31)
Hence, (-16) + (-15) = (-31)
Example 3 : Add (-311) and (-100)
Answer = Write the given integers in addition expression and we get:
(-311) + (-100)
Ignoring the Subtraction operator (-) and add the given integers (-311) and (-100) and we get
= 311 + 100 = 411
Now, since both the given integers are negative, so put Subtraction operator(-) on the left side of obtained integer
= -411
Hence, (-311) + (-100) = (-411)
Addition of more than two negative numbers
Example 4: Add following negative integers:
-10, -3, -15
Solution: Given negative integers are:
-10, -3, -15
Add the given integers, as we add whole numbers and we get:
(-10) + (-3) + (-15)
Add the integers, ignoring the subtraction operator (-) and we get:
= 28
Since given integers are negative integers, so put subtraction operator (-) and we get:
= (-28)
Hence, (-10) + (-3) + (-15) = (-28)
Example 5: Add following negative integers:
-9, -3, -11, -20
Solution: Given negative integers are:
-9, -3, -11, -20
Add the given integers, as we add whole numbers and we get:
(-9) + (-3) + (-11) + (-20)
Add the integers, ignoring the subtraction operator (-) and we get:
= 43
Since given integers are negative integers, so put subtraction operator (-) and we get:
= (-43)
Hence, (-9) + (-3) + (-11) + (-20) = (-43)
Example 6: Add following negative integers:
-12, -111, -24, -6, -70
Solution: Given negative integers are:
-12, -111, -24, -6, -70
Add the given integers, as we add whole numbers and we get:
(-12) + (-111) + (-24) + (-6) + (-70)
Add the integers, ignoring the subtraction operator (-) and we get:
= 223
Since given integers are negative integers, so put subtraction operator (-) and we get:
= (-223)
Hence, (-12) + (-111) + (-24) + (-6) + (-70) = (-223)
|